2010
DOI: 10.5688/aj7406106
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Students' Approaches to Learning in Undergraduate and Graduate Entry Programs

Abstract: Objectives. To compare longitudinal data with previous cross-sectional data regarding Australian undergraduate pharmacy students' approaches to learning, and explore the differences in approaches to learning between undergraduate and postgraduate cohorts. Methods. Longitudinal, repeated measures design using a validated self-report survey instrument were used to gather data. Results. Undergraduate students' preferences for meaning directed, undirected, and reproduction-directed approaches to learning displayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 25 publications
(30 reference statements)
6
29
0
3
Order By: Relevance
“…Unfortunately, many students are unable to transfer and apply this knowledge successfully. 1,2 A longitudinal study of pharmacy students' critical-thinking skills found that while the skills of analyzing, synthesizing, and evaluating appeared to improve over the course of a pharmacy program, students' motivation to think critically did not. 3 Integrating reflective practices in pharmacy education offers a possible solution to bridging theory with practice.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, many students are unable to transfer and apply this knowledge successfully. 1,2 A longitudinal study of pharmacy students' critical-thinking skills found that while the skills of analyzing, synthesizing, and evaluating appeared to improve over the course of a pharmacy program, students' motivation to think critically did not. 3 Integrating reflective practices in pharmacy education offers a possible solution to bridging theory with practice.…”
Section: Introductionmentioning
confidence: 99%
“…This difference may be attributable to the range and number of resources in the module relating to these aspects of patient self-management, such as the video-recorded interviews, class discussion, and readings, compared with the theoretical component (1 online lecture). These results also may indicate pharmacy students' preference for adopting an application-directed approach to their studies, 11,12 which suggests a vocational orientation to their learning and a belief that learning is the use of knowledge. The results of the multiple-choice questions assessed at the conclusion of the module show that student knowledge was sustained over the course of the semester.…”
Section: Discussionmentioning
confidence: 89%
“…10 An earlier study showed that pharmacy students who are self-reflective in their learning environments and have skills in collaborative learning are best equipped to construct and apply knowledge, rather than simply to accumulate and reproduce it. 11,12 We sought to address the lack of relevant patient self-management curriculum content, multimediafocused students, and the need to ensure knowledge acquisition and construction by developing a patient-focused learning module incorporating online lectures and readings, video-recorded interviews of patient accounts, and classroom-based discussions.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research showed both cross-sectionally and longitudinally that pharmacy students preferred to learn through dependence on teacher-sourced strategies rather than self-sourced strategies, and that deep processing and critical thinking were not routinely favored by students. 34,42 The low ranking that the quality of having an interactive teaching style received may have resulted from the introduction of the online-recorded lecture system, which enables academics to record lectures and make them available to students electronically. Although all other pharmacy classes (workshops, tutorials, and laboratories) are face to face, no attendance is required at recorded lectures.…”
Section: Discussionmentioning
confidence: 99%